Diving response after a one-week diet and overnight fasting. Issue 1 (December 2016) - Ghiani, Giovanna; Marongiu, Elisabetta; Olla, Sergio; Pinna, Marco; Pusceddu, Matteo; Palazzolo, Girolamo; Sanna, Irene; Roberto, Silvana; Crisafulli, Antonio; Tocco, Filippo
Abstract Background We hypothesized that overnight fasting after a short dietary period, especially with carbohydrates, could allow performing breath-hold diving with no restraint for diaphragm excursion and blood shift and without any increase of metabolism, and in turn improve the diving response. Methods During two separate sessions, 8 divers carried out two trials: (A) a 30-m depth dive, three hours after a normal breakfast and (B) a dive to the same depth, but after following a diet and fasting overnight. Each test consisted of 3 apnea phases: descent, static and ascent whose durations were measured by a standard chronometer. An impedance cardiograph, housed in an underwater torch, provided data on trans-thoracic fluid index (TFI), stroke volume (SV), heart rate (HR) and cardiac output (CO). Mean blood pressure (MBP), arterial O2 saturation (SaO2 ), blood glucose (Glu) and blood lactate (BLa) were also collected. Results In condition B, duration of the static phase of the dive was longer than A (37.8 ± 7.4 vs. 27.3 ± 8.4 s respectively, P  < 0.05). In static phases, mean ∆ SV value (difference between basal and nadir values) during fasting was lower than breakfast one (−2.6 ± 5.1 vs. 5.7 ± 7.6 ml, P  < 0.05). As a consequence, since mean ∆ HR values were equally decreased in both metabolic conditions, mean ∆ CO value during static after fasting was lower than the same phase after breakfast (−0.4 ± 0.5 vs. 0.4 ± 0.5 L · min−1 respectively, P  < 0.05). At emersion, despite the greater duration of dives during fasting, SaO2 was higher than A (92.0 ± 2.7 vs. 89.4 ± 2.9 % respectively, P  < 0.05) and BLa was lower in the same comparison (4.2 ± 0.7 vs. 5.3 ± 1.1 mmol∙L−1, P  < 0.05). Conclusions An adequate balance between metabolic and splancnic status may improve the diving response during a dive at a depth of 30 m, in safe conditions for the athlete's health.